Design Of Kaplan-Type Micro Hydropower Plant In The Brantas River Flow, Batu City - Malang - Khusnul Khotimah Ayuningtiyas; Kurniawan, Muhammad Helmi (LPPM Institut Studi Islam Sunan Doe, 2023)
Micro hydro power plants are small power plants that use water as energy, and the initiative is a turbine. This generator system is very suitable for use in rural areas because this system is easy to manufacture, generates sufficient electricity, and production costs are relatively low. Based on the above, it is necessary to design turbines that support this process system, including Kaplan-type turbines. This study aims to determine how much power the turbine can generate. The methods used in this research are the planning method, the design method, the testing method, and the analysis method for the Kaplan turbine design results referring to the results of initial observations, which show the height of the waterfall. The primary data collection is carried out through direct observation of the research object to determine the geographic location conditions and the ideal micro hydro power plant path. A designed Kaplan-type water turbine is in such a way that there are no errors in the design (for example, the manufacturing costs), and a design is carried out. 1) with an output of 1.2 m3/s and head efficiency (Heff) = 18.9 m, specific rotation (Ns) = 153.3 rpm. Control swing height (B) = 0.069 m, and the Kaplan turbine were chosen for planning the Brantas river flow micro-hydro power plant, Batu City – Malang. The potential that can be generated based on manual calculations is 124 KW, 1500 rpm turbine rotation with an efficiency of 0.85% - 0.90%.